SiC‐Doped Ge2Sb2Te5 Phase‐Change Material: A Candidate for High‐Density Embedded Memory Application. (13th June 2018) - Guo, Tianqi; Song, Sannian; Song, Zhitang; Ji, Xinglong; Xue, Yuan; Chen, Liangliang; Cheng, Yan; Liu, Bo; Wu, Liangcai; Qi, Ming; Feng, Songlin
Abstract: Phase‐change memory is one of the most attractive solutions for embedded applications, thanks to the low cost of integration with current manufacturing processes and the good scaling behavior. Despite intensive research efforts that are devoted to the modification of Ge2 Sb2 Te5 (GST) phase‐change material, the obtained improvements are still unsatisfactory for high‐performance applications. In this paper, SiC‐modification is first introduced to enhance the amorphous stability of GST without sacrificing its transition speed. Several enhancements can be demonstrated, including better thermal stability (10‐year data retention above 120 °C), lower RESET voltage (about 3.0 V at 20 ns pulse width), reduced volume change (smaller than 3.0%), and expected operation cycles (more than 1.0 × 10 5 ). According to the findings, the local bonding nature of Ge/Te atoms can be tuned by C/Si dopants through forming CGe and SiTe bonds. Apart from strengthening the atomic binding network for desirable data retention, the element interdiffusion is also effectively controlled and suppressed. Together with finer grains, smaller density change, and more uniform morphology, the modified structure transition finally contributes to the reduced switching voltage and long‐term endurance. Hence, it is envisaged that SiC‐doped GST with such advantages will give a competitive option for high‐density and high‐performance embedded memory. Abstract : In this paper, SiC‐modification is first introduced to enhance the amorphous stability of Ge2 Sb2 Te5 by virtue of the formation of CGe and SiTe bonds. 10‐year data retention at 126 °C, a RESET voltage of 3.0 V, and more than 1.0 × 10 5 cycles are demonstrated. Hence, SiC‐doped Ge2 Sb2 Te5 with such advantages will give a competitive option for high‐density and high‐performance embedded memory.